The impact of social media in maintaining the heritage among society / Che Haisyah Che Hassan ... [et al.] - Che Hassan, Che Haisyah; Mahdi, Fatin Faziana; Badrol Din, Khairunnisya Hanis; Ismail, Nur Izzati; Shabudin, Nursy Aheera Farhanny; Misdom, Muhammad Zulhelmi
Culture and heritage are considered as the fundamental aspects underpinning a country's national identity and sovereignty. The cultural heritage of Malaysia are unique as they portray the vibrant, largely traditional communities thriving in a culture of tolerance, peace, diversity and continuity in the midst of modernization and social change. Social media is the collective of online communications channels dedicated to community while websites and applications dedicated to forums, micro-blogging, social networking and social bookmarking. The researcher is focusing on the impact of social media in maintaining the heritage among society. The research objectives for this study are • To study the contribution of social media in maintaining heritage among society. • To determine that social media can provide a true information in maintaining heritage among society. • To study the impact of social media in maintaining the heritage among society. These researches are using in-depth interview that requires a number of professional which expert in this field. Researcher will ask them questions regarding this topic since the researcher target audience are 6 people with age range from 13 to 50 years old. The interviewee will be chosen based on their educational, intellectual and their understanding about the topic of the research. People that researcher going to interview for this research are: • Communication and Media (Masscomm) Student - 18-20 years old • Lecturer of UiTM Alor Gajah- 35-50 years old • Secondary School Student - 13-17 years old Based on this study, the researcher can get an expectation from many sides for example every level of generations will have their own reasons or opinions in using the social network in their daily life. Plus, students who are still in secondary school normally will not notify the heritage of our country through the social network and the researcher expected that the old generation will be more alert about the heritage in our country through the social media.